Current account reversals in industrial countries: does the exchange rate regime matter? - Cosimo Pancaro (European Central Bank (ECB), 2013)
This paper studies current account reversals in industrial countries across different exchange rate regimes. There are two major findings which have important implications for industrial economies with external imbalances: first, triggers of current account reversals differ between exchange rate regimes. While the current account deficit and the output gap are significant predictors of reversals across all regimes, reserve coverage, credit booms, openness to trade and the US short term interest rate determine the likelihood of reversals only under more rigid regimes. Conversely, the real exchange rate affects the probability of experiencing a reversal only under flexible arrangements. Second, current account reversals in advanced economies do not have an independent effect on growth. This result holds not only for industrial economies in general but also for countries with fixed exchange rate regimes in particular.
Keywords: F32; F41; 330; current account; exchange rate regime; reversals